An approach to inter-organizational workflow management in an electronic institution - Cardoso, Henrique (2010)
In a virtual organization, different business partners (individual organizations) cooperate in order to achieve a common goal. The coordination of the corresponding inter-organizational workflow is an important issue. In this paper an approach towards managing the operational embodiment of a manufacturing consortium is presented. This approach is conceptualized as a service within an Electronic Institution framework providing several agent-based services related with the formation and operation of virtual organizations. The behavior of the inter-organizational workflow management service is presented, modeled as an extension to a contract monitoring service. The paper also deals with the information exchange needs between these services and with the partners involved in a virtual organization contractual relationship.